Mortality of Chir Pine Trees by Insect Borers in Morni Hills , Haryana - a Case Study - Singh, Ranjeet; Goraya, G. S.; Singh, Charan; Kumar, Shalindra; Kumar, Surinder (Indian Forester, 2001)
Chir pine (Pinus roxburghii Sargent) is a very important indigenous conifer species of lower hills of Himalayas and the Shiwalik mountain range. A request to study the causes of mortality of Chir pine in Morni Forest Range under the Pinjore Forest Division in Haryana was received from the Conservator of Forests and the same have been investigated. It has been observed that the forest tract has been badly abused in past due to high biotic pressure , recurrent fires and heavy resin tapping by French Cup and Lip method. The resin tapping in the said forest has been stopped since 1983. However , the scars of the past injuries have left a permanent mark on these trees , which have over the years and due to recurrent fires lost their viability and have become prone to heavy insect borers infestation. So the immediate cause of current mortality in this area has been found to be the heavy infestation of insect borers. The study showed that these affected trees were severely attacked by four types of insect borers viz. Shpaenoptera aterrima , Cryptorhynchus rufescens , Platypus biformis and Polygrphus longifolia , which badly damaged the bark and bast and girdled the tree. Various insect pest management strategies including the insecticidal application were recommended for protecting the trees from the insect borers and their by protect them from mortality.